By the definition of migration (Journal of actual problems of jurisprudence, 2019)
For the scientific sphere characterized by contradictions associated with a variety of definitions of migration. In science, no notion of how migration has so many different interpretations, which in the modern conceptual turnover has a total of more than thirty. A study on the definition of migration, have historical, sociological, political science, economic, legal nature, which in turn determines the semantic diversity of approaches in defining the phenomenon.The article analyzes the position of authors in the definition of migration and migration attempts to classify the definitions found in the research literature.Key words: migration, the migration process, the migration mobility, migration flows, relocation, displacement.